The Adaptation of Indonesian Students in Malaysia - Kamal, Muhammad Rezky Syahputra; Ayuningtyas, Fitria (Universitas Merdeka Malang, 2024)
Adapting to a new environment is not easy for some people. Malaysia is a country that many people think has a very similar culture and language to Indonesia which makes many people think that adapting to the culture and language in Malaysia is an easy thing. This research aims to find out how Indonesian students studying at Universiti Sains Malaysia adapt to the culture and language that exist there. The method used in this research is descriptive qualitative in which the researcher wants to examine this research without changing the actual conditions of the phenomenon to be researched. This research conducted by the phenomenological method Husserl. The final result of the research obtained from this research is the discovery of varied methods from informants to be able to adapt to culture and communication in Malaysia, to be precise at Universiti Sains Malaysia. Unlike what we expected, the reality faced by the informants in adapting was something that was not so easy, even though the culture and language shared between the two countries were not that far apart.